PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP PRODUK PANGAN INDUSTRI RUMAH TANGGA YANG TIDAK BERLABEL DI KABUPATEN ENREKANG - Asram AT Jadda (FAKULTAS HUKUM UM PAREPARE, 2019)
The development and expansion of ecenomy especially in the sector of nasional industry and trading have been produce all kinds of goods snd services that can be consumend. That condition makes the position of consumer and producer aren’t balance. The main factor which being weakness for consumer is the consciousness bout their right are still low. One of the rights for consumer is information roghts, it forms food label but there are still can be found products from home industries food label in food in fact. That purpose from this research is know legal protection for the consumer againts unlable home industry’s food product and responbillity from producer unlabel home industry’s food. The research uses normative law receach. The writer uses legislation nd concept approach. The law data taken from primary, secondary, tertiary law. It will be analyzed a prescriptive that extend argumentation of the result as the writer did the research. From the research, it can be conclude that the legal protection for consumer about home i dustries food product which have not label that is preventive legal protection. Sanction related to food labeling only administrative sanction